Advances in CFD-based fluid computational dynamics for fruit tree model construction method and airflow regulation equipment - Lu, Haocheng; Li, Xue; Xu, Tao; Qi, Yannan; Yuan, Quanchun; Qiu, Wei; Lyu, Xiaolan (International Journal of Agricultural and Biological Engineering, 2025)
Due to its ability to broaden the transport channel of droplets within the plant canopy and enhance their penetration capacity, air-assisted spray technology is widely used in orchard pesticide application. To achieve uniform distribution of pesticide droplets in the tree canopy and obtain a higher pesticide utilization rate, it is crucial to clarify the coupling mechanism of the airflow field and droplet field generated by the air-assisted sprayer. This paper introduces a three-dimensional modeling method of the fruit tree canopy based on CFD (Computational Fluid Dynamics), offering a theoretical basis for analyzing the airflow demand calculation during different growth periods of the canopy. It also examines the interaction between canopy modeling and airflow, highlighting advancements in airflow regulation equipment and the effects of airflow speed and volume on spraying. The study shows that the precise regulation of airflow velocity and discharge rate is of importance for improving spraying efficiency. It finally points out that future research should focus on developing intelligent regulation equipment for efficient airflow-droplet control, using biomass sensing, which involves measuring the growth characteristics of the tree canopy, to meet the needs of orchards with diverse growth stages and canopy structures. This article could provide guidance for the future study of precision air-assisted spraying technology in orchards. Key words: airflow-assisted technology; airflow field; fruit tree canopy modeling; airflow regulation; airflow-droplet co-regulation DOI: 10.25165/j.ijabe.20251802.9554 Citation: Lu H C, Li X, Xu T, Qi Y N, Yuan Q C, Qiu W, et al. Advances in CFD-based fluid computational dynamics for fruit tree model construction method and airflow regulation equipment. Int J Agric & Biol Eng, 2025; 18(2): 1–8.